2015
DOI: 10.1155/2015/350196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Change of Deposition Time on the Secondary Direction and Abnormal Shape of Grains Growth of SnO2Thin Films

Abstract: SnO2thin films were grown on Si substrate using the low pressure chemical vapor deposition method. Observations made through electron microscopy indicate that thin films tend to grow with a constant direction when deposited at a temperature of 420°C for 5, 10, 20, or 30 min. However, when the deposition time increases, the particles forming the thin films are subject to a secondary growth. Observations made under a high-resolution transmission electron microscope reveal the lattice shape characteristic of thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Nevertheless, the increase of Pb particle size can still induce other effects in the horizontal direction, that is, certain stress can be generated and therefore more interfacial defects or even certain film deformation could result (which can be referred to from Figure S4 in the Supporting Information). Furthermore, some structural change also emerges with the deposition time of Pb, as shown in the XRD pattern in Figure c. For t Pb < 400 s, only pure CsPbBr 3 phase is detected.…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, the increase of Pb particle size can still induce other effects in the horizontal direction, that is, certain stress can be generated and therefore more interfacial defects or even certain film deformation could result (which can be referred to from Figure S4 in the Supporting Information). Furthermore, some structural change also emerges with the deposition time of Pb, as shown in the XRD pattern in Figure c. For t Pb < 400 s, only pure CsPbBr 3 phase is detected.…”
Section: Resultsmentioning
confidence: 92%
“…Jeong et al [ 10 , 11 ] reported that the growth direction of the thin film may change according to the initial growth conditions of thin films. The initial growth condition can be an important parameter in the grain growth of thin films, and changes in the growth surface of the thin film will change the particle shape, particle size, and electrical characteristics of the thin film [ 12 ].…”
Section: Resultsmentioning
confidence: 99%